Management of business model transformations of economic entities in the digital economy - Hnatenko, Iryna A.; Orlova-Kurilova, Olga V.; Omarov, Elvin Shahin; Орлова-Курилова, Ольга Володимирівна (ПАТ "ВНЗ "Національна академія управління", 2025)
The article explores modern approaches to the management of business model transformations of enterprises in the context of the digital economy. It is substantiated that digital transformation encompasses not only technological changes, but also profound transformations in strategy, culture, management, structure and interaction with partners. The key structural levels of transformations are identified, performance indicators, industry-specific implementation features and critical success factors are outlined. It is shown that systemic management of digital changes provides enterprises with adaptability, innovation and competitive advantages in a dynamic environment
Менеджмент трансформацій бізнес-моделей суб’єктів господарювання у цифровій економіці
Keywords: transformation management; digital economy; business model; change strategy; digital technologies; ecosystem; analytics; organizational culture; flexibility; innovation